2013
DOI: 10.1371/journal.pone.0062757
|View full text |Cite
|
Sign up to set email alerts
|

miR-655 Is an EMT-Suppressive MicroRNA Targeting ZEB1 and TGFBR2

Abstract: Recently, the epithelial-to-mesenchymal transition (EMT) has been demonstrated to contribute to normal and disease processes including cancer progression. To explore EMT-suppressive microRNAs (miRNAs), we established a cell-based reporter system using a stable clone derived from a pancreatic cancer cell line, Panc1, transfected with a reporter construct containing a promoter sequence of CDH1/E-cadherin in the 5′ upstream region of the ZsGreen1 reporter gene. Then, we performed function-based screening with 470… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
84
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(92 citation statements)
references
References 51 publications
6
84
2
Order By: Relevance
“…The TargetScan database predicted Zeb-1 and TGFBR2 (type receptor of TGF-b) as the target of miR-655, and the direct link between them was validated by 3 0 -UTR assay. Consistently, overexpression of exogenous miR-655 could inhibit TGF-b-induced EMT by suppression of Zeb-1 and TGFBR2 expression in the PDAC cell line KP1N [50].…”
Section: Microrna and Emtmentioning
confidence: 56%
See 1 more Smart Citation
“…The TargetScan database predicted Zeb-1 and TGFBR2 (type receptor of TGF-b) as the target of miR-655, and the direct link between them was validated by 3 0 -UTR assay. Consistently, overexpression of exogenous miR-655 could inhibit TGF-b-induced EMT by suppression of Zeb-1 and TGFBR2 expression in the PDAC cell line KP1N [50].…”
Section: Microrna and Emtmentioning
confidence: 56%
“…miR-655 was shown to be EMT-suppressive miR by a cell-based reporter system employing a stable clone derived from Panc-1 transfected with a reporter construct containing a promoter sequence of E-cadherin in the 5 0 upstream region of the ZsGreen1 reporter gene [50]. The ratio of fluorescence intensity of ZsGreen1 was measured using 470 synthetic double-strand RNAs mimicking human mature miRNAs, and miR-655 was identified as a novel EMT-suppressive miR in PDAC cells.…”
Section: Microrna and Emtmentioning
confidence: 99%
“…Reduced expression or loss of the TGFβ type I and type II receptors (TGFBR1 and TGFBR2) has been reported in various types of cancer, including HCC (23)(24)(25). TGFBR2 has been identified as the direct target of numerous miRNAs, including miR-655, miR-520c, miR-373 and miR-211 (26). The results of the present study suggest that TGFBR2 is a novel target of miR-302d in HCC and may partially explain the mechanism by which miR-302d functions in HCC, and why TGFBR2 expression is reduced in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…reported that miRNAs promote invasion and metastasis through mediating EMT (18). In order to evaluate the function of miR-106b in inducing EMT in ESCC, we examined the mRNA and protein expression of the epithelial marker E-cadherin and the mesenchymal marker vimentin in EC-1 cells.…”
Section: Downregulation Of Mir-106b Expression Could Inhibit the Indumentioning
confidence: 99%